Sosialisasi Pembelajaran Sex Education Dan Pencegahan Penggunaan Narkotika Pada Anak Usia Dini Di Sekolah Amerta - Belantika Sheren Aurorita; Avivah Shafa Nada; Erika Nopa Yanti Br Marpaung; Meli Andriyani; Octo Iskandar (Lembaga Pengembangan Kinerja Dosen, 2024)
Drugs and promiscuity are one of the problem faced in Indonesia and are increasingly growing. Drug use is not only used among adults but has now spread among teenagers and young children. Drug use will not be far from promiscuity, especially among teenagers and school children, so many get married at young age. Socialization of sex education learning and prevention of naroctics use ini early childhood at Amerta school is a community service activity carried out at Amerta school located ini Rongsok Village, Bintara, West Bekasi in May 2024. The aim of this activity to equip and make children aware of the importance maintain their welfare and dignity by means of self- protection and also increase and also increase knowledge about the side effects of narcotics use.